2018
DOI: 10.14740/jh455w
|View full text |Cite
|
Sign up to set email alerts
|

Hypercalcemia With Disseminated Osteolytic Lesions: A Rare Presentation of Adulthood Acute Lymphoblastic Leukemia

Abstract: Osteolytic bone lesions and hypercalcemia without peripheral blasts B-cell acute lymphoblastic leukemia (B-ALL) are reported in children but rarely seen in adults. Herein, we described two patients with B-ALL presenting with hypercalcemia and symptomatic osteolytic bone lesions. They were treated by standard induction chemotherapy after correction of hypercalcemia with supportive measures. With this two case reports we would like to emphasize the importance of clinical awareness of hypercalcemia and osteolytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…More than 20% of children with ALL have bone pain at the onset, higher than that in adults with ALL. However, multiple bone destruction is rare in both children and adults with ALL ( 4 , 9 , 10 ). Among adult malignant tumors, multiple bone destruction incidence is 27%–35% in lung cancer, 25%–30% in breast cancer, 7%–30% in multiple myeloma, < 10% in malignant lymphoma, and < 1% in leukemia ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…More than 20% of children with ALL have bone pain at the onset, higher than that in adults with ALL. However, multiple bone destruction is rare in both children and adults with ALL ( 4 , 9 , 10 ). Among adult malignant tumors, multiple bone destruction incidence is 27%–35% in lung cancer, 25%–30% in breast cancer, 7%–30% in multiple myeloma, < 10% in malignant lymphoma, and < 1% in leukemia ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal manifestations are rare presenting features in adult patients with ALL [4]. The mechanisms leading to the lytic lesions in ALL remain uncertain [5]. Two general mechanisms explain malignancy-associated hypercalcemia, osteolytic lesions due to the direct invasion of the skeleton by tumor cells and the ectopic production of circulating factors that activate osteoclastic bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…CRAB like initial presentation mimicking active myeloma is uncommonly reported in the literature. [3][4][5][6][7][8][9][10][11][12][13][14][15][16] In this manuscript we describe a middle-aged female subject who presented with clinicoradiological and biochemical features secondary to metastatic breast cancer mimicking CRAB positive myeloma and present a comprehensive review of all such CRAB positive nonmyelomatous malignancies reported in the literature.…”
Section: Crab (Hypercalcemia [C] Renal Dysfunction [R] Anemia [A] Bon...mentioning
confidence: 99%
“…There were twenty-two cases of CRAB positive nonmyelomatous malignancies (M:F = 1:1) the details of which are briefly summarized in Table 1. [3][4][5][6][7][8][9][10][11][12][13][14][15][16] The median age at presentation was 58. G reversal was described in a case reported by Roy et al in a case of primary osseous Burkitt lymphoma.…”
Section: Crab (Hypercalcemia [C] Renal Dysfunction [R] Anemia [A] Bon...mentioning
confidence: 99%